Tenun Baduy Luar Sebagai Identitas dan Perwujudan Pikukuh Karuhun - Iza Mahendra; Kankan Kasmana (Universitas Komputer Indonesia, 2022)
The Baduy Luar tribe is one of the many tribes in Indonesia that produces garments in the form of woven fabrics they create. In the course of its development, the weaving of the Baduy Luar Tribe was gifted by the cultural anguish of the Baduy Tribe, who always respect the universe and nature that they preserve, which is part of the Pikukuh Karuhun that they carry out as adherents of Sunda Wiwitan. Pikukuh Karuhun is a way of life for the Baduy Tribe and is applied thoroughly in their lives, including woven fabrics made by the Baduy Luar Tribe. The woven fabrics of the Baduy Luar have gone through various developments, including the use of additional tools and manufacturing techniques using songket, which is used to make motifs and decorations on woven fabrics, and synthetic threads as a substitute material used to make woven fabrics. In addition to the development they have made of the woven fabrics they make, the Baduy Luar Tribe creates several cloth motifs that become the identity of the Baduy Luar Tribe and distinguish it from the Baduy Dalam Tribe, whose ancestors they respect and obey. The Baduy Luar tribe also instills their philosophy of life in some of the woven fabrics they make so that they have sacred values for the Baduy Luar tribe, such as the Adu Mancung weaving, which is specifically for the traditional events they carry out. Keywords: Cultural Wisdom; Nature and Cultural Conservation; Sunda Wiwitan; Weaving of the Baduy Luar Tribe